Trend in the use of mouthwashes as a biosecurity measure in dental care in the post COVID-19 context: narrative review - Rodas Fernández, Keyla Anthuanet Maritza (2022)
Objective: To know the trend in the use of mouthwashes as a biosafety measure for dental care for the post-COVID-19 context. Method: The bibliographic search was carried out in the EBSCO, Scopus, PubMed databases, in the Virtual Health Library, and in the Google Scholar search engine, some of the descriptors used were "mouthwashes", "COVID-19", “SARS-CoV-2”, “aerosols”, among others. Initially, 114 articles were selected, of which 19 were discarded in duplicate, 34 because they were not directly related to the objective of the study and 24 because they did not meet the inclusion criteria, to finally select 38 articles. Main results:  Both povidone-iodine and cetylpyridinium chloride had a virucidal effectiveness against SARS-CoV-2 of 99.99%. Overall conclusion: The use of povidone-iodine such as cetylpyridinium chloride is recommended before any dental procedure in order to effectively reduce the viral and microbial load, thus preventing the transmission of any infectious disease.